1991
DOI: 10.1002/pd.1970110824
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of polyhydramnios in early gestation: Indication for prenatal diagnosis?

Abstract: Previously published reports have indicated that idiopathic polyhydramnios may be associated with trisomies 18 and 21 and that chromosomal analysis is indicated. Furthermore, the natural history and fetal outcome of polyhydramnios diagnosed in early gestation have not been well delineated. We identified 138 pregnancies with polyhydramnios prior to 26 weeks' gestation. Of 131 complete cases, 21 were diagnosed as severe, 18 as moderate, and 92 as mild polyhydramnios. Congenital abnormalities were noted in 18 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 10 publications
3
14
0
1
Order By: Relevance
“…For example, duodenal atresia is not usually detected sonographically before 24 weeks of gestation [16]. Our data corroborate previous reports [17,18], i.e. as the severity of polyhydramnios increases so does the likelihood of detecting a congenital malformation.…”
Section: Discussionsupporting
confidence: 82%
“…For example, duodenal atresia is not usually detected sonographically before 24 weeks of gestation [16]. Our data corroborate previous reports [17,18], i.e. as the severity of polyhydramnios increases so does the likelihood of detecting a congenital malformation.…”
Section: Discussionsupporting
confidence: 82%
“…Trisomy 18 is the single most common chromosome abnormality in previous studies of polyhydramnios and accounted for 67% (10 of 15) of abnormal karyotypes in the present study. Snijders and colleagues; reported that 95% (19 of 20) fetuses with polyhydramnios and IUGR had abnormal karyotypes, and all but one of these were trisomy 18.…”
Section: Discussionsupporting
confidence: 53%
“…The latter was present in the two published cases by D'Amato Sizonenko et al (2002) and in the case reported by Avansino et al (1999). It is well documented that polyhydramnios is associated with various congenital (including chromosomal) abnormalities (Hendricks et al, 1991). The dysmorphic features include macrocephaly, enlarged anterior fontanel, epicanthus with apparent hypertelorism, midfacial hypoplasia with a small nose, micrognathia, short neck, low-set dysplastic ears with preauricular pits, and arachnodactyly.…”
Section: Discussionmentioning
confidence: 80%